Pemanfaatan Kapur Cangkang Keong Mas pada Air Rawa Media Pemeliharaan Ikan Lele dengan Model Budikdamber - Dade Jubaedah; Marsi; Feni Haryani; Wijayanti, Marini (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2024)
One of the currently developing urban farming models is budikdamber, which is a mutually beneficial combination of aquaculture and hydroponic systems with a bucket as a medium for cultivation. This research aims to find out the best dosage of golden snail shells lime for increasing the swamp water pH for rearing catfish (Clarias sp.) and kale using the budikdamber model. This research applied a completely randomized design with six treatments and three replications. The dosages of golden snail shells lime used as treatment consist of 0.00 mg L-1 equivalent to CaO (P0), 10 mg L-1 equivalent to CaO (P1), 20 mg L-1 equivalent to CaO (P2), 30 mg L-1 equivalent to CaO (P3), 40 mg L-1 equivalent to CaO (P4) and 50 mg L-1 equivalent to CaO (P5). The results of this study indicate that the best dose of golden snail shell lime is 20 mg L-1 equivalent to CaO (P2), which can optimize the swamp water pH from 4.80 to 6.78, survival rate 84 %, absolute weight growth of 18.44 g, absolute length growth of 6.15 cm and feed efficiency 132.49 %, and the total weight of the kale plant 11.33 g.